Tooth Surface Design and Solid Modeling of Offset Orthogonal Arc Tooth Face Gear - Zhanrong Feng; Lingfeng Gao; Ping Fang; Guangjin Xiong; Chao Luo (Jixie chuandong)
A new type of offset orthogonal face-gear is presented. A certain offset distance is applied to the arc tooth cylindrical gear， which is used as an imaginary tool to envelop the offset orthogonal arc tooth face-gear. Based on the differential geometry calculation and gear meshing principle， the equations of the offset orthogonal arc tooth face-gear surfaces are deduced， and the mathematical models of working tooth surface and transition surface are established in Matlab. By using the generated mathematical model， two different offset distances are applied. After analyzing the equations and comparing the tooth surface models， a conclusion is drawn， the effect of offset distance on tooth shape is mainly reflected in tooth height， but not in tooth width and tooth thickness. Finally， the set of tooth surface points is derived， and the solid modeling of offset orthogonal arc tooth face-gear is designed， which lays a foundation for the subsequent research on the meshing and bending strength of this kind of tooth.